In search of the recurrent units of translation - Macken, Lieve (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translation memory systems aim to reuse previously translated texts. Be-cause the operational unit of the first-generation translation memory sys-tems is the sentence, such systems are only useful for text types in which full-sentence repetition frequently occurs. Second-generation sub-sentential translation memory systems try to remedy this problem by providing addi-tional translation suggestions for sub-sentential chunks. In this paper, we compare the performance of a sentence-based translation memory system (SDL Trados Translator’s Workbench) with a sub-sentential translation memory system (Similis) on different text types. We demonstrate that some text types (in this case, journalistic texts) are not suited to be translated by means of a translation memory system. We show that Similis offers useful additional translation suggestions for terminology and frequent multiword expressions.